2017
DOI: 10.1111/een.12409
|View full text |Cite
|
Sign up to set email alerts
|

Host plant exodus and larval wandering behaviour in a butterfly: diapause generation larvae wander for longer periods than do non‐diapause generation larvae

Abstract: 1. Prior to pupation, lepidopteran larvae enter a wandering phase lasting up to 30 h before choosing a pupation site. Because stillness is important for concealment, this behaviour calls for an adaptive explanation.2. The explanation most likely relates to the need to find a suitable pupation substrate, especially in terms of shelter from predation, and given that many predators and parasitoids use host plants as prey-location cues, mortality probably decreases with distance from the host plant. Hence, remaini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…In the course of the 5th (last) instar, the larvae were weighed daily until cessation of feeding (the beginning of the wandering stage; e.g. [47]). This allowed us to record the maximal larval mass, and the day on which it was achieved.…”
Section: Methodsmentioning
confidence: 99%
“…In the course of the 5th (last) instar, the larvae were weighed daily until cessation of feeding (the beginning of the wandering stage; e.g. [47]). This allowed us to record the maximal larval mass, and the day on which it was achieved.…”
Section: Methodsmentioning
confidence: 99%
“…For example, many species burrow into the ground to pupate, which offers a refuge from the predators preying above the ground such as birds [17]. Before individuals enter the pre-pupal stage and start to spin their cocoon, they often disperse from their larval host plant or food source [9,24,38,39]. Staying close to the host plant can increase the risk of being detected by natural enemies that often use the host plant as a cue to locate their potential prey [13,40].…”
Section: Avoiding Detection By Visual Predatorsmentioning
confidence: 99%
“…Lepidopteran larvae have a wandering phase prior to pupation when larvae move away from their host plant while seeking a suitable substrate for pupation [38]. In the European swallowtail butterfly, Papilio machaon, this wandering phase is longer in the overwintering generation, which has a longer pupal stage, in comparison to larvae that are under direct development (non-overwintering larvae), which have a pupal stage of only one to two weeks.…”
Section: Avoiding Detection By Visual Predatorsmentioning
confidence: 99%
“…Moreover, if an individual who pupates under diapause at a location away from other conspecifics, cannibalistic attack is unlikely. Wiklund et al (2017) suggested that individuals of Papilio machaon who hibernate disperse further than those who do not diapause to escape from host-related predation. In nature, not only the balance between density and food conditions, but also the ability to disperse before pupation could be important for the survival of diapausing pupae in A. alcinous.…”
Section: Pupal Diapausementioning
confidence: 99%